Adoption and promotion of KMITL e-learning program for the elderly in urban Thailand - Debhavalya, Roselyn; Teetakaew, Torsangrasmee (Edelweiss Applied Science and Technology, 2025)
This study explores the acceptance and impact of the KMITL e-learning programs among elderly populations in urban Thailand. A total of 300 participants from retired and senior citizen clubs in Ladkrabang, Romklao, and Minburi districts were surveyed through a mixed-methods approach involving questionnaires, cognitive assessments, and expert interviews. The study assessed cognitive development, user satisfaction, and acceptance of digital learning platforms. Findings demonstrate high satisfaction with the platform’s content clarity, design accessibility, and learning flexibility. Courses focusing on social studies and digital media production were especially favored, reflecting the elderly’s growing interest in health preparation, financial security, and intergenerational communication. Statistically significant correlations were identified between prior technological experience, satisfaction levels, and the intention to continue online learning. The results affirm that thoughtfully designed online programs can successfully support lifelong learning and active aging among the elderly. Practical implications highlight the need for adaptive learning models, specialized course development, and policy initiatives to promote digital inclusion and enhance the quality of life for aging populations.